Writing the resistance on the eve of martyrdom: Rhetorical features in Hiba Abū Nadā's last Facebook posts (Gaza, 7-20 October 2023) - Wartiman; Mhd. Rizalman; Laurence Lingat Ramos; Mohammad Ridhan Alhafidz; Hajar Essamlali (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
During the final fourteen days of her life, Hiba Abū Nadā published 67 posts on her personal Facebook page from within the Gaza bombing zone, a corpus that closed on the day she was killed in an Israeli airstrike. Research on balāghah has so far concentrated on resistance literature composed at some remove from the events it depicts, leaving unexamined how the classical Arabic rhetorical system operates when produced in real time under genuine mortal threat. Addressing that gap, this qualitative descriptive-analytical study identifies the balāghah figures that predominate in Abū Nadā's posts, drawing on the classical framework of al-Jurjānī and Ibn al-Athīr to classify and decompose three figurative units: isti'ārah 'metaphor', kināyah 'metonymy', and tashbīh 'simile'. The analysis identified 39 figures: 20 isti'ārah (11 tashrīḥiyyah, 9 makniyyah), 9 kināyah, and 10 tashbīh. Isti'ārah predominates through a shift of wahān 'tenor' from the concrete to the existential domain; tashbīh balīgh prevails by collapsing comparative distance; and kināyah, although least frequent, proves the most argumentatively dense. These findings constitute early textual evidence of how Arabic balāghah functions when a trained writer confronts her own mortality in real time, extending the tradition of Palestinian resistance literature into a register that earlier generations, writing from exile, were never required to occupy.